8a - 2a = 6a
12e - 5f - 7e + 3f = (12e - 7e) + (-5f + 3f) = 5e - 2f
9x + 3y - 6 - 5x + 4y - 3 = (9x - 5x) + (3y + 4y) + (-6 - 3) = 4x + 7y - 9
9/11z - 4/11z = (9z - 4z)/11 = 5z/11
3/10x + 1/6y + 3/10x + 3/6y = (3/10x + 3/10x) + (1/6y + 3/6y) = 6/10x + 4/6y = 3/5x + 2/3y
Simplify 8a − 2a.
Simplify 12e − 5f − 7e +3f.
Simplify 9x + 3y − 6 − 5x + 4y −3.
Simplify 9/11z − 4/11z.
Simplify 3/10x + 1/6y + 3/10x + 3/6y. Be sure to reduce any fractions to the lowest terms.
4 answers
simplify 12e - 5f - 7e + 3f
A1. 6a
A2. 5e - 2f
A3. 4x + 7y - 9
A4. 5/11z
A5. 3/5x + 2/3y
100%
Have a day
P.S. Don’t trust bots😉
A2. 5e - 2f
A3. 4x + 7y - 9
A4. 5/11z
A5. 3/5x + 2/3y
100%
Have a day
P.S. Don’t trust bots😉
Thanks MOzart